Prolonged-release melatonin for insomnia – an open-label long-term study of efficacy, safety, and withdrawal - Lemoine P; Garfinkel D; Laudon M; Nir T; Zisapel N (Dove Medical Press, 2011)
Patrick Lemoine1, Doron Garfinkel2, Moshe Laudon3, Tali Nir3, Nava Zisapel3,41The Clinique Lyon-Lumière, Meyzieu, France; 2Geriatric-Palliative Department, Shoham Geriatric Medical Center, Pardes Hanna, Israel; 3Neurim Pharmaceuticals Ltd, Tel-Aviv, Israel; 4Department of Neurobiology Faculty of Life Sciences, Tel Aviv University, Tel Aviv, IsraelBackground: Prolonged-release melatonin (PRM) 2 mg is indicated for insomnia in patients aged 55 years and older. A recent double-blind placebo-controlled study demonstrated 6-month efficacy and safety of PRM in insomnia patients aged 18–80 and lack of withdrawal and rebound symptoms upon discontinuation.Objective: To investigate the efficacy, safety, and withdrawal phenomena associated with 6–12 months PRM treatment.Methods: Data from a prospective 6–12-month open-label study of 244 community dwelling adults with primary insomnia, who had participated in a placebo-controlled, double-blind dose-ranging trial of PRM. Patients received PRM nightly, followed by a 2-week withdrawal period. Main outcome measures were patient-reported sleep quality ratings (diary), adverse events, vital signs, and laboratory tests recorded at each visit, and withdrawal symptoms (CHESS-84 [Check-list Evaluation of Somatic Symptoms]). Nocturnal urinary 6-sulfatoxymelatonin excretion, a measure of the endogenous melatonin production, was assessed upon discontinuing long-term PRM.Results: Of the 244 patients, 36 dropped out, 112 completed 6 months of treatment, and the other 96 completed 12 months of treatment. The mean number of nights by which patients reported sleep quality as "good" or "very good" was significantly higher during PRM than before treatment. There was no evidence of tolerance to PRM. Discontinuation of PRM was not associated with rebound insomnia or withdrawal symptoms; on the contrary, residual benefit was observed. PRM was well tolerated, and there was no suppression of endogenous melatonin production.Conclusion: Results support the efficacy and safety of PRM in primary insomnia patients aged 20–80 throughout 6–12 months of continuous therapy. PRM discontinuation even after 12 months was not associated with adverse events, withdrawal symptoms, or suppression of endogenous melatonin production.Keywords: PRM, adverse events, sleep, insomnia, patients